Comparative study of hyaluronic acid fillers by in vitro and in vivo testing. (16th March 2013) - Park, K.Y.; Kim, H.K.; Kim, B.J.
Abstract Background Numerous hyaluronic acid (HA) fillers seem to have similar characteristics, although manufacturers insist that monophasic and biphasic HA fillers are different in many ways. Little information regarding this is available in the literature. Objectives To determine characteristics of monophasic fillers vs. biphasic fillers. Material and methods We tested three different (two biphasic and one monophasic) HA fillers both in vitro and in vivo. In the in vitro assay, cell toxicity, resistance to enzyme degradation, syringeability and morphology of particles were tested. In vivo, the efficacy and safety were investigated in the dorsal skin of hairless mice. Results There was no cell toxicity in any of the three HA fillers. Resistance to enzymatic degradation and syringeability were better in the two biphasic HA fillers than in the monophasic filler. In particle morphology test, gel type monophasic HA filler was also found as a particle type, although there was a slight difference. Volume assessment in animal skin was superior with the monophasic than with the two biphasic HA fillers. Conclusion Biphasic HA fillers have some advantages in hyaluronidase resistance, syringeability and lower risk for overcorrection, while monophasic HA fillers may be more suitable for volume augmentation due to swelling capacity.